Laser sideband cooling with positive detuning - Schwedes, Christian; Becker, Thomas; von Zanthier, Joachim; Walther, Herbert; Peik, E (Physical Review A, 2004)
An experimental and theoretical study of laser sideband cooling of a trapped ion in a radiofrequency trap is presented. The influence of the micromotion in the time-dependent potential of a Paul trap can lead to a counterintuitive situation, where sideband cooling is possible for positive values of the laser detuning, i.e., for a laser frequency that is higher than the resonance frequency of the ion at rest. The cooling rate and the capture range are calculated in a semiclassical model. Experimental results of laser sideband cooling at positive detuning are demonstrated with a single trapped In+ ion stored in a miniature Paul trap.